Modified hybrid PWM technique for cascaded MLI and cascaded MLI application for DTC drive - Mahmoud Samy; Mohamed Mokhtar; Naggar Hassan Saad; Ahmed Abd El-Sattar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Multilevel inverter is increasingly utilised for DC/AC conversion in multiple electrical power applications due to its wide capabilities, low switching losses, and reduced output harmonics. Multilevel inverter faces some problems related to complex control, and high number of components. This paper presents a modified multilevel inverter topology that needs only three DC sources and eight switches to generate thirteen voltage levels. This high number of voltage levels enhances the multilevel inverter performance significantly. Also, this paper introduces a modified modulation technique to trigger the multilevel inverter switches. This modified technique is called Hybrid pulse width modulation. The modified multilevel inverter topology accompanied by the improved modulation methodology leads to a multilevel inverter of smaller size, simpler control, and staircase sinusoidal output waveform with noticeable reduction in the harmonics content without using any harmonics filter. Furthermore, the proposed multilevel inverter topology will be utilized along with a direct torque control (DTC) induction motor drive to emphasize its characteristics by improving the motor drive performance. Correspondingly, this research runs a comprehensive set of simulations to validate the features of these topology and modulation methodology through MATLAB/Simulink environment software.